Stability constants and thermodynamic behaviour of the complex formation of two crown ethers with zinc (II) and copper (II) ions in water + acetonitrile mixed solvent: a conductivity measurement study. (4th March 2022) - Hossain, Md. Alamgir; Hossen, Md. Delwar; Mahbub, Shamim; Hoque, Md. Anamul; Islam, D.M. Shafiqul; Kumar, Dileep; Khan, Javed Masood; Irfan, Mohammad; Ahmed, Mohammad Z
ABSTRACT: We have investigated the behaviour of change of molar conductivity of mixtures of two crown ethers (CE) (18-Crown-6; 18C6 and 24-Crown-8; 24C8) and metal ions (M n+ ) (Zn 2+ and Cu 2+ ) and the complexation between CE and M n+ in water + acetonitrile binary solvent system (20, 40, 60 and 80%; v/v) at 298.15 K to 328.15 K by conductometric technique. K f values for all complexes were found to be decreased with enhancement of temperature. Complexes associated with Zn 2+ exhibit a trend of K f : 24C8 + Zn 2+ > 18C6 + Zn 2+ in 20% solvent composition (water-acetonitrile) and order of 18C6 + Zn 2+ > 24C8 + Zn 2+ was found for 80% solvent composition. However, logarithm values of K f for the Cu 2+ complexes were found to obey the order of 24C8 > 18C6 almost for all compositions except with a few exceptions. Δ G o was found to be negative indicating spontaneous complexation between CE and M n+ .